Chrześcijańska codzienność ludzi świeckich w twórczości pisarskiej ks. Franciszka Grudnioka (1920–1998) - Maciejewski, Waldemar (Studia Pastoralne, 2026)
Franciszek Grudniok’s writings show several aspects of Christian life. Saying prayers and conducting religious practices, which lead to holiness in everyday life, are the major ones. A prayer is described as the foundation of Christian life. Listening to the Word of God and obeying it in everyday life is a special kind of prayer. The author presents a great value of the Word of God in the course of Christian development. An important aspect in Christian life is proper experience of Eucharist and confession as the basic sacraments. These two factors let people develop spiritual life. Next, the paper presents Grudniok’s view on human suffering. It is shown as a kind of mystery which is difficult to describe. The topic was familiar to Franciszek Grudniok. He wanted to present suffering as a treasure of spiritual life. Finally, several forms of spiritual life suggested by Franciszek Grudniok to lay persons are presented. Spirituality of St. Mary, Eucharistic spirituality as well as the spirituality of various Saints are shown in the paper.